Analysis of emissions and residue from methods to improve efficiency of at-sea, in situ oil spill burns. (December 2021) - Aurell, Johanna; Holder, Amara; Gullett, Brian; Lamie, Nathan; Arsava, Kemal; Conmy, Robyn; Sundaravadivelu, Devi; Mitchell, William; Stone, Karen
Abstract: The combustion efficiency of simulated at-sea surface oil burns (in situ burns) was determined in a 63 m 3 tank while testing varied boom configurations and air-assist nozzles in the presence and absence of waves. Combustion efficiencies of Alaska North Slope oil based on unburned carbon in the plume emissions ranged from 85% to 93% while values based on oil mass loss ranged from 89% to 99%. A four-fold variation in PM2.5 emission factors was observed from the test conditions. The most effective burns in terms of reduced emissions and post-burn residue concentration of total petroleum hydrocarbons were those that had high length to width boom ratios resulting in higher flame front surface area exposure to ambient air. The amount of oil mass lost was not related to any combustion efficiency parameters measured in the plume, representing a potential tradeoff between unburnt oil and air pollution. Graphical abstract: Unlabelled Image Highlights: Potential tradeoff between air pollution and residual oil during in situ burns. PM2.5 emissions ranged four-fold, indicating effects of burn conditions. Higher boom length:width ratio reduced emissions and residual hydrocarbons. The presence of waves decreased the oil mass loss.